ANALISIS PERGESERAN STRUKTUR EKONOMI DAN SEKTOR UNGGULAN DI KABUPATEN TABALONG TAHUN 2013-2017 - HUSAINI HUSAINI; SYAHRITUAH SIREGAR (PPJP Universitas Lambung Mangkurat, 2019)
This research aims to find out how are the conditions of shifting economic structure and which sectors are the leading sectors in Tabalong Regency.This research uses a calculating change in the value of sectoral contributions to the formation of GDP, location quotient, dynamic location quotient, classic shift share. By using secondary data in the form of GDP according to employment at constant prices.The results of the study indicate a shift in the economic structure in Tabalong Regency, namely the traditional sector (primary) to the modern sector (tertiary and secondary). And when the mining and quarrying sector's contribution is calculated, there are five leading sectors in Tabalong Regency. The sector is processing, construction, providing accommodation and eating, industrial real estate and other services. But when the mining and quarrying sector contribution was eliminated there were only two superior sectors in Tabalong Regency. The sector includes construction and provision of accommodation and food for drinking. It is known based on the superior criteria of LQ, DLQ, industrial mix (PS) and competitive advantage (DS) which have the highest value among several sectors. Keywords : Structural shift, Leading Sector, Location quotient, Dynamic location quotient, Classic shift share.